2013
DOI: 10.1002/jms.3215
|View full text |Cite
|
Sign up to set email alerts
|

Modified MALDI MS fatty acid profiling for bacterial identification

Abstract: Bacterial fatty acid profiling is a well-established technique for bacterial identification. Ten bacteria were analyzed using both positive- and negative-ion modes with a modified matrix-assisted laser desorption ionization mass spectrometry (MALDI MS) approach using CaO as a matrix replacement (metal oxide laser ionization MS (MOLI MS)). The results show that reproducible lipid cleavage similar to thermal in situ tetramethyl ammonium hydroxide saponification/derivatization had occurred. Principal component an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…The multilocus sequence analysis of these three B. ceti Mediterranean strains indicates that they also belong to the dolphin type of the ST26 cluster.Up to now, all B. ceti Mediterranean strains stem in a separate branch from the main MLVA16 A1 and A2 clusters of B. ceti isolates from dolphins inhabiting the Atlantic Ocean. Although the number of analysed Mediterranean B. ceti strains by MLVA16 is still low to draw a definitive branching order, the taxonomical position of these newly defined strains [11] is supported by proteome analysis and, to a less extent, by fatty acids analysis, two robust techniques used in bacterial taxonomy [33] and useful for characterization of Brucella [9-11,24,31,32]. Therefore, it seems that the B. ceti isolates described here belong to a particular genotype prevalent in the Mediterranean Sea.…”
Section: Discussionmentioning
confidence: 99%
“…The multilocus sequence analysis of these three B. ceti Mediterranean strains indicates that they also belong to the dolphin type of the ST26 cluster.Up to now, all B. ceti Mediterranean strains stem in a separate branch from the main MLVA16 A1 and A2 clusters of B. ceti isolates from dolphins inhabiting the Atlantic Ocean. Although the number of analysed Mediterranean B. ceti strains by MLVA16 is still low to draw a definitive branching order, the taxonomical position of these newly defined strains [11] is supported by proteome analysis and, to a less extent, by fatty acids analysis, two robust techniques used in bacterial taxonomy [33] and useful for characterization of Brucella [9-11,24,31,32]. Therefore, it seems that the B. ceti isolates described here belong to a particular genotype prevalent in the Mediterranean Sea.…”
Section: Discussionmentioning
confidence: 99%
“…The CaO cleaved lipids to fatty acid Ca adducts in positive‐ion MS and fatty acid anions in negative‐ion mode with reproducibility similar to saponification results . Linear discriminant analysis of data from ten bacterial species analyzed using CaO in both positive‐ and negative‐ion modes showed greater than 94% correct assignment …”
mentioning
confidence: 52%
“…(b) and (c) show the DART spectra of the phospholipids, myristoyl‐distearoyl‐glycerol and palmitoyl‐dioleoyl‐glycerol, which likewise contained a peak for the FAs. In catalytic studies involving metal oxide laser ionization (MOLI)‐MS, the intensity of the observed FAs in phospholipids was a function of the fatty acid position . The 2‐position fatty acid peak was 2× the intensity of the peak from the fatty acid in the 1‐position.…”
Section: Resultsmentioning
confidence: 99%
“…Other attempts have made use of metal oxides such as ZnO, MnO, CoO, WO 3 , TiO 2 , SnO 2 , Fe 3 O 4 , CaO, and NiO; and bare metals such as Au, Ag, Sn, and Al . Clearly, the use of metal oxides as a base for LDI has been investigated for several compounds, and the Vorhees' research lab, responsible for studies using CaO and NiO, have coined this work as metal oxide laser ionization mass spectrometry (MOLI) …”
Section: Introductionmentioning
confidence: 99%
“…Other attempts have made use of metal oxides such as ZnO, MnO, CoO, WO 3 , TiO 2 , SnO 2 , Fe 3 O 4 , CaO, and NiO; and bare metals such as Au, Ag, Sn, and Al. [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Clearly, the use of metal oxides as a base for LDI has been investigated for several compounds, and the Vorhees' research lab, responsible for studies using CaO and NiO, have coined this work as metal oxide laser ionization mass spectrometry (MOLI). [47][48][49] In addition to the ability to efficiently absorb UV incident laser radiation and then transfer that energy to desorb and ionize a target analyte without any unintended ions formed, there are other characteristics of inorganic particles to consider that make them successful in assisting LDI of a target analyte.…”
Section: Introductionmentioning
confidence: 99%